2016
DOI: 10.1038/nm.4189
|View full text |Cite
|
Sign up to set email alerts
|

Efficient derivation of microglia-like cells from human pluripotent stem cells

Abstract: Microglia, the only lifelong resident immune cells of the central nervous system (CNS), are highly specialized macrophages which have been recognized to play a crucial role in neurodegenerative diseases such as Alzheimer’s, Parkinson’s and Adrenoleukodystrophy (ALD). However, in contrast to other cell types of the human CNS, bona fide microglia have not yet been derived from cultured human pluripotent stem cells. Here we establish a robust and efficient protocol for the rapid production of microglia-like cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
581
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 527 publications
(598 citation statements)
references
References 50 publications
15
581
1
1
Order By: Relevance
“…Induced pluripotent stem cells are an attractive candidates for the treatment of neurodegenerative disorders due to their capacity to differentiate into a wide array of relevant phenotypes, including neural precursor cells, neurons, and vascular endothelial cells, upon addition of induction factors such as retinoic acid (Yuan et al, 2013; Muffat et al, 2016). iPSC neural progenitor cells have been found to spontaneously differentiate into neurons and astrocytes in vitro , expressing high levels of β-tubulin and glial fibrillary acidic protein (GFAP) (Paşca et al, 2015).…”
Section: Identifying the Optimal Cell Type For Stem Cell Transplanmentioning
confidence: 99%
See 1 more Smart Citation
“…Induced pluripotent stem cells are an attractive candidates for the treatment of neurodegenerative disorders due to their capacity to differentiate into a wide array of relevant phenotypes, including neural precursor cells, neurons, and vascular endothelial cells, upon addition of induction factors such as retinoic acid (Yuan et al, 2013; Muffat et al, 2016). iPSC neural progenitor cells have been found to spontaneously differentiate into neurons and astrocytes in vitro , expressing high levels of β-tubulin and glial fibrillary acidic protein (GFAP) (Paşca et al, 2015).…”
Section: Identifying the Optimal Cell Type For Stem Cell Transplanmentioning
confidence: 99%
“…In terms of neuroinflammation, iPSCs may play a significant role. A recent in vitro study showed that iPSCs could differentiate into microglia, the primary immunoregulatory cell type in the brain (Muffat et al 2016). Moreover, a study by Hague and colleagues found that iPSCs could develop into antigen-specific regulatory T cells (Tregs), a T cell type involved in the suppression of autoimmunity (Haque et al, 2016).…”
Section: Identifying the Optimal Cell Type For Stem Cell Transplanmentioning
confidence: 99%
“…as in mouse microglia. Finally, we believe that the recent success in obtaining microglia-like cells from human pluripotent stem cells 51 should greatly aid this translational work, and even make it possible to investigate changes in channel expression in a broader disease specific context.…”
Section: Future Directions Toward An Integrated View Of Kmentioning
confidence: 99%
“…Microglia, which arise via primitive myelopoiesis, are also essential in neuronal maturation and development of the central nervous system. A recent report described the generation of microglia-like cells from human PSCs that integrate into a 3D organotypic neuroglial environment and respond to cellular damage (Muffat et al, 2016). Incorporation of PSC-derived microglia into cerebral organoids will provide an unprecedented opportunity to study the interactions between primitive myeloid-derived cells and early brain development.…”
Section: Interactions Between Multiple Germ Layers Improve In Vitro Cmentioning
confidence: 99%